2012
DOI: 10.1128/mcb.06365-11
|View full text |Cite
|
Sign up to set email alerts
|

Remodelers Organize Cellular Chromatin by Counteracting Intrinsic Histone-DNA Sequence Preferences in a Class-Specific Manner

Abstract: The nucleosome is the fundamental repeating unit of eukaryotic chromatin. Here, we assessed the interplay between DNA sequence and ATP-dependent chromatin-remodeling factors (remodelers) in the nucleosomal organization of a eukaryotic genome. We compared the genome-wide distribution of Drosophila NURD, (P)BAP, INO80, and ISWI, representing the four major remodeler families. Each remodeler has a unique set of genomic targets and generates distinct chromatin signatures. Remodeler loci have characteristic DNA seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
89
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(103 citation statements)
references
References 65 publications
13
89
0
1
Order By: Relevance
“…Interestingly, two related complexes, BAPand PBAP, share six subunits but differ in the signature subunits: Osa, dD4, and TTH for BAP; PB, BAP170, SAYP, and dBRD7 for PBAP (Fig. 8A) (Moshkin et al 2007;Moshkin et al 2012). The 'core complex" in the absence of these signature subunits is not functional in vivo.…”
Section: Diversity Of Nucleosome Remodeling Complexesmentioning
confidence: 99%
“…Interestingly, two related complexes, BAPand PBAP, share six subunits but differ in the signature subunits: Osa, dD4, and TTH for BAP; PB, BAP170, SAYP, and dBRD7 for PBAP (Fig. 8A) (Moshkin et al 2007;Moshkin et al 2012). The 'core complex" in the absence of these signature subunits is not functional in vivo.…”
Section: Diversity Of Nucleosome Remodeling Complexesmentioning
confidence: 99%
“…An interesting observation arising from our study is that loci classified as DNA-directed have higher GC content; while loci classified as DNA-independent have lower GC content. It has been previously demonstrated that GC content confers different requirements for ATP-dependent chromatin remodelers (RamirezCarrozzi et al 2006(RamirezCarrozzi et al , 2009Moshkin et al 2012). SWI/SNF-independent genes have greater GC content around the TSS, whereas SWI/SNF-dependent genes have lower GC content.…”
Section: Nucleosome Redistributions Are Widespread and Transientmentioning
confidence: 99%
“…This observation is consistent with multiple studies that have investigated a role for the ISWI family of chromatin remodelers. Genomic targets of ISWI family members have increased GC content (Moshkin et al 2012). Additionally, studies in yeast and flies have shown that in the absence of ISWI complexes, nucleosomes adopt DNA-encoded positions (Gkikopoulos et al 2011;Moshkin et al 2012).…”
Section: Nucleosome Redistributions Are Widespread and Transientmentioning
confidence: 99%
See 1 more Smart Citation
“…5a). The work of Moshkin et al (2012)) extended this concept, demonstrating that although ISWI target sites are predicted to be favourable for nucleosome formation because of an high GC content, ISWI remodellers tend to remove nucleosomes from the target loci, thus antagonizing in vivo and in vitro the DNA sequence driven nucleosome placement. ChIP-on-chip experiments suggested that dISWI preferentially binds nucleosome free regions located in close proximity to Transcriptional Start Site of genes, supporting the potential regulatory role played by the DNA sequence underlying the remodeller target site in the recruitment and the biological functions of dISWI (Sala et al 2011).…”
Section: Iswi Post-translational Modificationsmentioning
confidence: 99%